Coordination of Effectiveness in Implementing Public Services: Study in Sumbergempol District, Tulungagung - Muharsono Muharsono; Teguh Pramono; Zulfaisya Nurhalimah (Universitas Padjadjaran, 2023)
This study aims to determine how effective coordination is in the implementation of public services, especially in Sumbergempol District and Tulungagung. Public service refers to a service activity conducted by government officers (apparatus) who must provide the best service to the community to create community welfare. This study used the descriptive-qualitative research method. Researchers use data collection techniques in the form of interviews, observations, and documentation. While data analysis and interpretation are carried out by the analysis process, which is data reduction, data display, and conclusion. The results showed that coordination in the implementation of public services in Sumbergempol District generally has been running well, yet the results have not been effective. From the results of this study, it can be concluded that public services in Sumbergempol District and Tulungagung Regency need changes to improve public service efforts so that the results are more effective.